EFEKTIVITAS TUTON TERHADAP KEMANDIRIAN DAN CAPAIAN HASIL BELAJAR MAHASISWA FKIP UNIVERSITAS DARUSSALAM AMBON PADA MATA KULIAH PENGANTAR APLIKASI KOMPUTER - Haris Kolengsusu; Randi Hasim Latukau; John Karuwal (LPPM Universitas Muhammadiyah Muara Bungo, 2022)
Constraints encountered during online practicum in the Introduction to Computer Applications Course, namely, an unstable network that causes communication gaps between students and lecturers during practicum, limited facilities (laptops) owned by students, inadequate internet quota, student learning abilities and independence different ways of operating the software. The purpose of this study was to determine the effectiveness of online tutorials on independence and achievement of student learning outcomes of FKIP UNIDAR introductory computer application courses. This research is a pre-experimental design research type One-Shot Case Study with the subjects of FKIP students of Chemistry Education, Physics Education, Mathematics Education and Biology Education courses taking introductory courses on computer applications for the 2021/2022 even academic year. Data on the validity of online tutorials and student learning independence were obtained through the distribution of questionnaires, while the cognitive aspects were obtained through post-test. The results obtained indicate that online tutorials are effectively used as a practical medium in online learning, with the acquisition of student learning outcomes 78.57% getting good grades and student learning independence after learning through online tutorials is in the good category.